Investigation on the heating performance of the heat pump with waste heat recovery for the electric bus. (June 2020) - Han, Xinxin; Zou, Huiming; Wu, Jiang; Tian, Changqing; Tang, Mingsheng; Huang, Guangyan
Abstract: Efficient heating system is critical for electric vehicles to extend the driving range. In this paper, an air source heat pump system with waste heat recovery (WHR) for the electric bus was proposed to improve the heating performance. According to the experimental results of the prototype, it's found that the pressure drop of waste heat exchanger (WHX) has great effects on the heating performance and the heat exchanger is required to be optimized. The simulation model of this series system was developed and validated to study the heating performance of the series waste heat recovery system with low pressure drop WHX. The simulation results showed that heat recovery can improve the heating performance at the ambient temperature of −5 °C. Compared with the vapor injection heat pump without WHR, the heating capacity and COP of the heat pump at 2 kW waste heat were increased by 1.61% and 1.38%, respectively. The improvements of heating capacity and COP at 6 kW waste heat were 5.12% and 2.56%, respectively. As the ambient temperature is lower than 0 °C, the heating performance of heat pump system with 2 kW waste heat is better than that of system without WHR. However, as the ambient temperature rises, the heating performance of heat pump with WHR becomes worse. Highlights: A heat pump with waste heat recovery for the electric bus was proposed. The system model was developed and validated with the experimental dates. The pressure drop of waste heat exchanger has a significant effect on the series waste heat recovery system. Waste heat recovery has advantages as ambient temperature is lower than 0 °C.